HAK KEKAYAAN INTELEKTUAL (HAK CIPTA) SEBAGAI OBJEK WARIS DALAM HUKUM PERDATA - Prasetyo, Ramadhio Adi (Fakultas Hukum Universitas Islam Indonesia, 2022)
This study aims to analyze and determine the criteria for intellectual property rights (copyright) as objects of inheritance in civil law and to analyze and determine the status of intellectual property rights (copyright) as objects of inheritance in civil law. Intellectual property rights are material rights, rights to objects originating from the work of the brain, the result of the work of the ratio. The result of the work of reasoning human ratios. The result of his work is in the form of immaterial objects, intangible objects, for example, copyrighted songs. Article 16 paragraph (1) Law no. 28 of 2014 concerning Copyright stipulates that by its nature copyright is an intangible movable object. Immaterial property rights are property rights whose objects are intangible objects (intangible objects). In this case many things can be used as objects of property rights which are included in the scope of incorporeal objects. For example, billing rights, rights arising from the issuance of securities, rental rights and so on. The results of the study concluded that copyright (copy rights) which is part of Intellectual Property Rights has criteria as an object of inheritance, because copyright law determines copyright as an intangible movable object that gives moral rights and economic rights to its creators which are exclusive which can be transferred to his heirs. Copyright (copy rights) which is part of Intellectual Property Rights (IPR) according to civil law has the position of an object of inheritance, because the law of inheritance is regulated in book II of the Civil Code which regulates objects. Inheritance object according to civil law is an object that is the property of someone who died.